2021
DOI: 10.1186/s12885-021-08782-9
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic efficacy of inhibiting MYCN and mTOR signaling against neuroblastoma

Abstract: Background Neuroblastoma (NB) patients with MYCN amplification or overexpression respond poorly to current therapies and exhibit extremely poor clinical outcomes. PI3K-mTOR signaling-driven deregulation of protein synthesis is very common in NB and various other cancers that promote MYCN stabilization. In addition, both the MYCN and mTOR signaling axes can directly regulate a common translation pathway that leads to increased protein synthesis and cell proliferation. However, a strategy of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In addition to triggering apoptosis, JQ1 suppressed EC cell growth by inducing G1 cell cycle arrest. JQ1 has been reported to cause human neuroblastoma cell cycle arrest in G1 phase mainly by inhibiting the MYCN and mTOR signaling pathways [ 22 ]. JQ1 also decreases the proportion of cells in G2 phase and increases the share of cells in G1 phase in a preclinical model of pancreatic cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to triggering apoptosis, JQ1 suppressed EC cell growth by inducing G1 cell cycle arrest. JQ1 has been reported to cause human neuroblastoma cell cycle arrest in G1 phase mainly by inhibiting the MYCN and mTOR signaling pathways [ 22 ]. JQ1 also decreases the proportion of cells in G2 phase and increases the share of cells in G1 phase in a preclinical model of pancreatic cancer [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also observed several interesting phenomena. (1) Studies have shown that inhibiting mTOR signaling could deregulate MYCN-driven proliferation [14,18,19]. However, in this study, dual pan-class I PI3K and mTOR kinase inhibitor BEZ-235 [53] could deregulate mTOR activity but did not decrease the expression level of MYCN, indicating that regulating MYCN through mTOR may as well require another co-factor, such as mitochondrial inhibition.…”
Section: Discussionmentioning
confidence: 60%
“…Since the MYCN protein has not been directly druggable, an indirect inhibition of MYCN expression by targeting upstream or downstream components of the MYCN pathway is considered an alternative therapeutic option [13][14][15][16]. Oliynyk et al showed that MYCN induction upregulates the activity of glycolytic enzymes and mitochondrial oxidative phosphorylation in neuroblastoma [17], indicating that MYCN amplified childhood neuroblastoma could be more dependent on functional mitochondria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the time course of research, it became evident that simultaneous inhibition of multiple targets could prove useful in the treatment of neuroblastoma. For example, a recent study has reported that the simultaneous inhibition of MYCN and mTOR using bromodomain extra-terminal protein inhibitors and temsirolimus manifested significant cell survival suppression [ 219 ]. Another study showed that the use of PARP and CHK1 inhibitors synergized to induce death in neuroblastoma cells and in primary cultures of MYCN amplified and MYCN overexpressing cells [ 220 ].…”
Section: Molecular Mechanistics Of the Mycn Genementioning
confidence: 99%